La santé en situation linguistique minoritaire - Bouchard, Louise; Gaboury, Isabelle; Chomienne, Marie-Hélène; Gilbert, A.; Dubois, L. (Politiques de Santé, 2009)
fs-ref-orig: Bouchard, L., Gaboury, I., Chomienne, M.-H., Gilbert, A. et Dubois, L. (2009). La santé en situation linguistique minoritaire. Politiques de Santé, 4(4), 36-42. https://www.ncbi.nlm.nih.gov/pmc/Article de revue s/PMC2700700/pdf/policy-04-036.pdf fs-code-orig: Bouchard-2009a

Vieillir en situation linguistique minoritaire au Canada et ses implications pour la santé [infographie] - Gagnon-Arpin, Isabelle; Bouchard, Louise; Gaboury, Isabelle; Bourbonnais, V.; Chomienne, Marie-Hélène (2009)
fs-ref-orig: Gagnon-Arpin, I., Bouchard, L., Gaboury, I., Bourbonnais, V. et Chomienne, M.-H. (2009). Vieillir en situation linguistique minoritaire au Canada et ses implications pour la santé [infographie]. Réseau de recherche interdisciplinaire sur la santé des francophones en contexte minoritaire au Canada (RISF), Université d’Ottawa. fs-code-orig: Gagnon-Arpin-2009a

Physical inactivity among Francophones and Anglophones in Canada - Imbeault, Pascal; Makvandi, Ewa; Batal, Malek; Gagnon-Arpin, Isabelle; Grenier, Jean; Chomienne, Marie-Hélène; Bouchard, Louise (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)
Objective Leisure-time physical activity participation is influenced by various socio-demographic factors. Recent evidence suggests that being part of a minority negatively impacts an individual’s health status. The objective of this study was to compare inactive leisure-time physical activity between the Francophone minority and the Anglophone majority in Canada. Methods Data from the fusion of cycles 2.1, 3.1, 4.1, 2008 and 2009 of the Canadian Community Health Survey (CCHS) were used. The linguistic variable was determined by languages spoken at home, first language learned and still understood, language of interview, and language of preference. Leisure-time physical activity was based on a questionnaire provided during the interview. Factors associated with inactive leisure time were examined using logistic regression models. Results Francophones were more likely than Anglophones to be physically inactive in their leisure time (49.1% vs. 47.2%). A greater percentage of Francophones had poor self-perceived health, were older, were single, had lower education, had higher rate of unemployment and lived in rural areas compared to Anglophones. When these socio-demographic factors were taken into account, there were no further differences in the likelihood of being inactive between Francophones and Anglophones. Conclusion The Francophone minority in Canada is characterized by socio-demographic factors that have a negative impact on leisure-time physical activity participation.

Comparison of dietary intake between Francophones and Anglophones in Canada: Data from CCHS2.2 - Batal, Malek; Makvandi, Ewa; Imbeault, Pascal; Gagnon-Arpin, Isabelle; Grenier, Jean; Chomienne, Marie-Hélène; Bouchard, Louise (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)
Objective To compare the dietary intake and food choices between Francophone Canadians in a state of linguistic minority (outside of Quebec) and the English-speaking majority. Methods We used the 2004 Canadian Community Health Survey (CCHS) cycle 2.2 (general health and 24-hour dietary recalls) to describe dietary intake of Francophone Canadians (excluding Quebec) and compare them to the English-speaking majority. The linguistic variable was determined by languages spoken at home, first language learned and still understood, language of interview, and language of preference. The mean differences in daily nutrient and food intake were assessed by t and chi-square tests. Results Differences in total energy and daily food intakes by language groups were not observed in the sample; however, significant differences in weekly consumption were found in different age and sex categories: lower fruits and vegetables consumption, and vitamins and macronutrients intakes for older Francophone men and higher intakes of energy and saturated fat from “unhealthy” foods for Francophone men 19–30 years of age. Based on the Acceptable Macronutrients Distribution Range (AMDR), approximately 50% of the sample exceeded their acceptable energy intake from saturated fats, and 80% were below their required intake of linoleic fatty acid. Conclusion We confirmed that belonging to Francophone minorities in Canada affects food choices and nutritional well-being of this population. The most vulnerable groups identified by our study were Francophone men in the youngest (19-30) and older (50 and over) age categories. The extent to which the cultural setting influences the diet and, in turn, the health of the minority population needs further examination.

Prévalence de la dépression majeure chez les arthritiques des populations canadiennes : étude comparative entre anglophones majoritaires et francophones en situation linguistique minoritaire - Fotsing, Salomon; Nzokem, Aubain H.; Grenier, Jean; Imbeault, Pascal; Batal, Malek; Bouchard, Louise; Chomienne, Marie-Hélène (Revue canadienne de santé publique / Canadian Journal of Public Health, 2013)
Objectif La santé mentale et l’arthrite sont deux maladies reconnues comme étant des enjeux majeurs en santé publique. La situation minoritaire des francophones est reconnue comme un déterminant de la santé. L’objectif de cette étude est de déterminer la prévalence de la dépression majeure chez les arthritiques adultes des populations francophones minoritaires comparativement à la majorité anglophone. Méthode Analyse secondaire de l’ESCC (fusion de 2003 (cycle 2.1), 2005 (cycle 3.1), 2007 (cycle 4.1), 2008 et 2009) excluant le Québec. La variable langue a été construite selon un algorithme pré-existant réunissant la langue maternelle, de conversation, d’entrevue et de préférence. La dépression majeure était définie selon les critères du DSM IV. La présence ou non d’arthrite était une variable auto-rapportée. Les prévalences et rapports de cotes pour la dépression dans la population arthritique ont été calculés et ajustés en fonction de divers facteurs (socioéconomiques, isolement social, accès aux services de santé). Résultats L’étude identifiait 159 426 anglophones et 10 658 francophones. Parmi les sujets avec arthrite (27 %), la prévalence de la dépression était de 8,5 % et de 8,4 % chez les francophones et les anglophones, respectivement; chez les hommes, les anglophones étaient plus à risque de faire une dépression que les francophones: OR=2,36 (IC 95%: 2,07-2,70) c. OR=1,87 (IC 95%: 1,20-2,91). Cette tendance ne se retrouvait pas chez les femmes. Conclusion Notre échantillon démontre que dans une population arthritique, la dépression semble toucher plus particulièrement les hommes anglophones. Cependant il faut souligner la petite taille de l’échantillon.

Comorbidités entre maladies chroniques et problèmes de santé mentale fréquents : différences entre francophones et anglophones - Grenier, Jean; Gosselin, Dominique; Greenman, Paul. Samuel; Chomienne, Marie-Hélène; Imbeault, Pascal; Batal, Malek; Bouchard, Louise (Psy-Cause, 2016)